Attitude and intention of migrant populations in the Netherlands regarding female genital mutilation/cutting - Ramin Kawous; Emily Allwood; Annemarie Middelburg; Anke van der Kwaak; Diana Geraci; Marthine Bos; Maria E. T. C. van den Muijsenbergh (BMC, 2022)
Plain English summary Female genital mutilation/cutting (FGM/C), also known as female circumcision, is a practice which involves the cutting away of part or the whole of the external female genital organs. The practice has no health benefits, and it harms girls and women in many ways. The migration of girls and women to high-resource countries such as the Netherlands, has led to the development of programs to prevent FGM/C and to care for those affected by FGM/C. The purpose of this study was to explore the attitude and intention of migrant populations in the Netherlands towards FGM/C. The results of this study may be relevant in the development of interventional programs to promote the elimination of FGM/C. Our findings showed that the study participants had no intention to perform FGM/C on their daughters. Many participants may have changed their attitudes towards the abandonment of FGM/C. The social pressure to perform FGM/C seems to be lower in the Netherlands when compared to the country of origin, however, some pressure to perform FGM/C still exist after migration. In this regard, educational programs are necessary, with an emphasis on empowering vulnerable groups such as newly arrived migrants in facing social pressure.